How Competent Are Our Students in Digital Entrepreneurship? - Vladimir Simovic; Mirna Safi; Aleksandra Bradić-Martinović; Hamsa Sarhan; Rupalli Bhagat; Djina Ivanovic (Proceedings, 2023)
This paper provides insights into the research design and preliminary results of the research targeting digital entrepreneurial competence levels of the university students acquired during the course of formal university education. The preliminary insights represent the part of the research grant funded by Kuwait Foundation for Advancements in Sciences aiming to develop the tool for assessing the levels of students digital entrepreneurial competences. The preliminary results indicate that there are differences in digital entrepreneurial competence levels which can be attributed to different characteristics of university students.